Precocious Puberty: A Case Report - Anna Felita; Ivanna Sarahfebi; Anastasia Nadya; Parbati Anjali; Chandni P. Daryanani (Rumah Sakit Unggul Karsa Medika, 2022)
Background Puberty is a transitional period in children with acceleration of growth and development of secondary sexual characteristics. When this period appears before the age of 8 to 9 years in children, it is called precocious puberty. Depending on the primary source of the hormonal production, precocious puberty may be classified as central (gonadotropin dependent or true) or peripheral (gonadotropin independent or precocious pseudo-puberty). Case presentation We herein report a case of precocious puberty in a 7,5-year-old girl who has shown early sign of secondary sexual development. Patients complained pain on her nipple, her breasts began to grow in size, and changes in her body odour, but had no complaints about her pubic hair growth and any vaginal discharge. Laboratory findings shown high level in fertility hormones and level of bone age is equal to 10-year-old girl. Patient then had begun to receive monthly therapy of Leuprolide. Conclusion Detailed history taking on chronological order of thelarche, pubarche, menarche, and adrenarche, followed by assessment on family history, nutritional history, child developmental history, medication history, and neurological complaints should be done in order to diagnose precocious puberty. Physical examination and other examination of bone age determination, Luteinizing Hormone and Follicle-Stimulating Hormone level, and pelvic ultrasound are essentials in defining the diagnosis and treatment. Leuprolide is indicated for Central Precocious Puberty patient who have advanced bone age at the time of initial evaluation. As a clinician, it is necessary to diagnose precocious puberty as soon as possible to have good prognosis for the patient.